Infodemic amidst the Covid-19 in the Philippines: Spotted By Vera Files.Org - Sabonsolin, John Cavin M. (Future Science / FSH-PH Publications, 2022)
This study analyzes the infodemic in the Philippines during the intense lockdowns during the early stages of the covid-19 pandemic. With the said lockdown, people are observed to be more present in social media. World Health Organization pronounced that